RELATIONSHIP BETWEEN THE DELAY IN MAKING A TIMELY DECISION TO SEEK MEDICAL ASSISTANCE AND PERINATAL MORTALITY IN LURAMBI AND BUTERE SUB-COUNTIES, KAKAMEGA COUNTY, KENYA - Simiyu, Catherine; Kipmerewo , Mary; Arudo, John (Global Journal of Health Sciences, 2021)
Purpose: To determine the relationship between the delays in making a timely decision to seek medical assistance and perinatal mortality in Lurambi and Butere sub-counties, Kakamega County, Kenya. Methodology: A community based retrospective cross-sectional research design was adopted using mixed methods for data collection. A total of 520 respondents were randomly selected from 40 out 830 villages of Lurambi and Butere sub-counties using multistage cluster sampling. The respondents were interviewed from November 2017 to March 2018. Data entry and analysis was done using SPSS Version 21 software. Descriptive and inferential statistical analyses were used. Bivariate and multivariate logistic regressions were applied and adjusted odds ratio was used to determine the strength of association. A p-value of â‰¤ 0.05 was considered as statistically significant. Findings: Education level (p<0.02) and employment status (p<0.03) of mothers influenced perinatal mortality. Wrong action taken during an experience of antenatal complication (AOR= 0.6; 95% CI: 0.1 - 0.9; p = 0.03), emergency unpreparedness (AOR=0.1; 95%CI: 0.04-0.42; p=0.0007) and, lack of recognition of newborn danger signs (AOR=01; 95%CI: 01-0.4; p<0.0001) were significantly associated with perinatal mortality. Birth preparedness and complication readiness during pregnancy and childbirth, based on the study findings reduce delay in obtaining care. Strengthening maternal education and social support system along the continuum of care during pregnancy, delivery and post-natal periods is paramount to ensure newborn survival. Unique Contribution to Theory, Practice, and Policy: Unique factors are that apart from medical interventions, strengthening maternal education and social support system along the continuum of care during pregnancy, delivery and post-natal periods is paramount to ensure newborn survival in Lurambi and Butere sub counties. Interventions to promote informed decisions regarding maternal and newborn care with a strong social support system are critical. These results contribute to maternal and newborn health care practice and policy change that if implemented could result in a reduction of perinatal mortalities.